2021
DOI: 10.3390/polym13030367
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Thermosensitive Hydrogel Used to Extinguish Class A Fire

Abstract: Hydrogels are crosslinked polymers that become fully swollen when placed in aqueous environments. They are widely used in the field of firefighting because they can remarkably increase the viscosity and wettability of water. In this study, a thermosensitive hydrogel used to effectively suppress class A fire was synthesized by using methylcellulose, sodium polyacrylate, and magnesium chloride. The structure, surface activity and viscosity of the hydrogel were characterized. Fire extinguishing performance was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This method may be useful in deformulation studies of unknown precursor and crosslinking chemistry and is applicable to more complex polymeric networks crosslinked with different chemistries, such as those formed from paint formulations . Finally, the method also reveals insights about the thermal decomposition properties of the crosslinked material under study, which could be important for hydrogels used under extreme conditions, for example, in fireproof materials and for fire extinguishing. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method may be useful in deformulation studies of unknown precursor and crosslinking chemistry and is applicable to more complex polymeric networks crosslinked with different chemistries, such as those formed from paint formulations . Finally, the method also reveals insights about the thermal decomposition properties of the crosslinked material under study, which could be important for hydrogels used under extreme conditions, for example, in fireproof materials and for fire extinguishing. , …”
Section: Discussionmentioning
confidence: 99%
“…68 Finally, the method also reveals insights about the thermal decomposition properties of the crosslinked material under study, which could be important for hydrogels used under extreme conditions, for example, in fireproof materials and for fire extinguishing. 69,70 The presented methodology establishes a novel analytical route for the qualitative analysis of crosslinked polymeric networks. Relative quantitation is also possible by comparing similar networks prepared under different conditions to determine the extents of crosslinking versus unreacted (unlinked) loops.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Cheng et al [23,24] prepared intelligent gels by polymerizing organics to achieve good thermal stability and high toughness. Li et al [25,26] proposed fire extinguishing gels that used methylcellulose as a basic material to achieve high water absorption and temperature sensitivity. Han et al [27] prepared a new biomass gel foam based on sodium alginate, calcium L-lactate, alkyl glycoside, and tea saponin in order to create an environmentally friendly fire prevention and extinguishing material for coal mines.…”
Section: Introductionmentioning
confidence: 99%
“…The wettability of smart materials triggered by a small change in temperature resulting in altering their hydrophilic–hydrophobic properties is required [ 20 ]. Ma et al [ 21 ] found that the surface tension of a methylcellulose/sodium polyacrylate/magnesium chloride decreased after phase transition, enhancing its capability to wet the wood and the fire extinguishing efficiency. Gels with porous structure can promote not only swelling capacity but also water-retaining capacity and mechanical strength [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%